The library collection of the Waqf of Ahmed Agha in Mostar from the mid-17th century - Adnan Kadrić; Muamer Hodžić; Madžida Mašić (Bosniaca)
Goal: The paper will present the library collection of the Babusaade Ahmed Agha based on one of the three existing waqfiyas of this benefactor, preserved in the Topkapi Palace Museum in Istanbul (TS.MA.d. 6927). The waqfiya describes the establishment of a madrasa and its accompanying library in Mostar in the mid-17th century. The work will also offer a comparison of this collection with the Gazi Husrev-beg Library collection in Sarajevo, as the majority of the preserved titles from the mentioned collection can be found in this central heritage institution. Approach/Methodology: Using the identification method, we determined the exact titles and authors of the endowed books and manuscripts, for which numerous lexicographical dictionaries and manuscript catalogs were consulted. The classification of works by subject areas was based on the Flügel and Ahlwardt models. Regarding the presence of works from the original collection established by the Babusaade Ahmed Agha, the main research base was the Gazi Husrev-beg Library collection in Sarajevo, which provided direct access to works from the mentioned collection, as well as published catalogs of manuscripts in Oriental languages from this institution. Results: The paper highlights data related to the titles and authors of works from the library collection that was part of this educational institution. Based on this information, insight was provided into the thematic and content diversity of the mentioned library. Particularly interesting is the fact that this waqfiya contains the oldest mention of a librarian (1653) in Mostar, along with his duties and responsibilities regarding the preservation of the manuscript collection. In addition to this, the paper discusses the current state of the collection, aiming to determine the extent of preservation of the manuscript holdings from this 17th-century Mostar library. Originality/Value: In scientific and expert circles, it was known that there was a waqf established by the Babusaade Ahmed Agha, but it was not widely known what he left behind as a legacy for his fellow citizens in Mostar. This paper specifically discusses his legacy in Mostar based on primary sources, as well as the provisions he established to specify how this waqf would function. The waqf of Ahmed Agha was very important for the cultural life of Mostar in the second half of the 17th century.